Status and problems of the national accelerated manpower training program in two training centers in Cagayan - Santiago, Consuelo (Abad) 1923- ([Quezon City s.n.], 1972)
This paper discussed the status and problems of the accelerated manpower training programs in the Cagayan Valley Agricultural College and the Cagayan Valley College of Arts and Trades to serve as bases for drawing up some implications for their improvement.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Vocational education -- Philippines -- Cagayan; Labor and laboring classes -- Education. -- Philippines